FORMULATION OF CARBON EMISSION REDUCTION STRATEGY THROUGH SWOT AND AHP ANALYSIS AT PUPUK ISKANDAR MUDA COMPANY - Dedy Sulastono; Udisubakti Ciptomulyono (LPSDI Bina Patria, 2025)
The industrial sector is a major contributor to carbon emissions, driving the greenhouse effect and global warming. Pupuk Iskandar Muda (PIM) Company, as a petrochemical company, is committed to reducing carbon emissions through enhanced energy efficiency and low-emission technology adoption, although its carbon emissions remain high and have significantly increased. This study aims to identify internal and external factors influencing PIM's Company carbon emission reduction strategy and to determine the optimal priority strategy. The research uses a quantitative descriptive method. The respondents are employees of Pupuk Iskandar Muda Company, selected using the purposive sampling technique, resulting in a sample size of 11 people. The research data includes primary data obtained from observations, interviews, and questionnaires, while secondary data is gathered from supporting literature. Data analysis techniques include SWOT analysis, Analytical Hierarchy Process (AHP), and post-risk-based strategy. The research results identified 12 alternative strategies, with two prioritized alternatives selected as the best options based on a post-risk internal strategy analysis, incorporating financial mitigation considerations. These prioritized strategies are: